BETWEEN RELIGION, CONFLICT, AND CHILDREN: A Narrative Study of Religious Moderation in the Ahmadiyah Case of Sintang - Kurniawan, Heri; Sulaiman, Rusdi; Fahmi, Reza (International Journal of Multidisciplinary Reseach, 2025)
The 2021 destruction of an Ahmadiyya place of worship in Balai Harapan Village, Sintang Regency, West Kalimantan, represents a vivid example of ongoing religious conflict in Indonesia. This conflict reflects not only interfaith tensions but also leaves deep psychosocial impacts, particularly on children living near the site. This study aims to describe the conflict narrative, analyze religious moderation practices as a resolution strategy, and identify the psychological impact on children as indirect victims of conflict. Using a qualitative approach with a narrative case study design, data were collected through in-depth interviews, observation, and document review. The findings reveal that local religious moderation practices successfully reduced tensions temporarily, but failed to address the structural roots of the conflict. Affected children exhibited mild to moderate trauma symptoms without receiving professional intervention. This study underscores the urgency of integrating religious moderation with child protection policies in the context of religious-based conflicts.